Intervention empowerment of families in preventing and controlling overweight and obesity in children: A systematic review - Fransiskus Geroda Mado; Saifuddin Sirajuddin; Masyta Muis; Ida Leida Maria; Darmawansyah Darmawansyah; Muhammad Alwi Arifin (Journal of Public Health Research, 2021)
There have been an increasing overweight and obesity in very anxious children. Furthermore, obesity is a condition that occurs due to the accumulation of excess or abnormal fat. This disorder is believed to be the most significant public health problem that affects children in the 21st century. This study aimed to examine the literature review, articles and research results analyzing the effectiveness of family or parent empowerment interventions through health education. Many research articles were searched on several databases such as PubMed and PreQuest, using the following keywords which include "family empowerment", "overweight", "obesity", "health lifestyle", "BMI", "children", "RCT" starting from 2014 to 2019. The searched results obtained 162 articles on family empowerment, overweight and obesity. Out of the 162 articles, 20 were selected that discussed family empowerment interventions for overweight and obesity. Critical analysis of the 20 articles was carried out based on design, sample, treatment, parameters, findings and conclusions. The literature review analysis showed that family empowerment interventions in the form of health education or promotion activities vary widely in terms of methods, components, duration, individuals involved, specificity and effectiveness. Furthermore, this intervention consists of training activities, courses, and teaching practices. Statistical analysis showed that all these methods significantly increased the ability and independence of the family in controlling overweight and obesity. In conclusion, health education interventions that are packaged in various programs are proven to significantly improve the ability of families or parents in preventing and controlling overweight and obesity in children.